2013
DOI: 10.1590/0037-8682-0104-2013
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of American tegumentary leishmaniasis in special populations: a summary of evidence

Abstract: Revista da Sociedade Brasileira de Medicina Tropical 46(6):669-677, Nov-Dec, 2013http://dx.doi. org/10.1590/0037-8682-0104-2013 Address to: Dr a Juliana Saboia Fontenele e Silva. Lab. ABSTRACT We aimed to assess and synthesize the information available in the literature regarding the treatment of American tegumentary leishmaniasis in special populations. We searched MEDLINE (via PubMed), EMBASE, LILACS, SciELO, Scopus, Cochrane Library and mRCT databases to identify clinical trials and observational studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 105 publications
0
11
0
2
Order By: Relevance
“…Allometric dosing of miltefosine have been proposed as an alternative to improve drug exposure in children, and its safety is being evaluated currently for VL patients (NCT02431143 and NCT02193022); however, little is known about feasibility or safety of alternative dosing regimens for antimonials. Despite these facts, meglumine antimoniate is still the first line treatment in all age groups in Colombia, which highlights the urgent need to reconsider the management of pediatric cutaneous leishmaniasis with improved dosing or alternative treatments [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Allometric dosing of miltefosine have been proposed as an alternative to improve drug exposure in children, and its safety is being evaluated currently for VL patients (NCT02431143 and NCT02193022); however, little is known about feasibility or safety of alternative dosing regimens for antimonials. Despite these facts, meglumine antimoniate is still the first line treatment in all age groups in Colombia, which highlights the urgent need to reconsider the management of pediatric cutaneous leishmaniasis with improved dosing or alternative treatments [26]. …”
Section: Discussionmentioning
confidence: 99%
“…In previous studies in Paraná State, Silveira et al (7) , Castro et al (8) , and Curti et al (14) reported a higher prevalence of ATL in patients aged 15-49 years, whereas Pontello et al (17) reported an associated age of 21-40 years. According to Silva et al (18) , the ATL incidence in individuals aged >65 years has increased significantly in Brazil. In fact, in the present study, 19.5% of the patients were aged >60 years and 6 deaths occurred in individuals aged ≥59 years, including 1 registered in the SINAN as due to ATL.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for pregnant women are particularly limited in leishmaniasis patients. The use of pentavalent antimonials, pentamidine and miltefosine is contraindicated in pregnancy (FDA categories C, C and D, respectively), and thus the only treatment options are paromomycin (no category assigned) and AMB (FDA category B) (reviewed in Fontenele e Silva et al [ 112 ]). The physiological changes in pregnant women are known to possibly alter the ADME of drugs and could thus potentially affect the exposure to drugs.…”
Section: Specific Patient Populationsmentioning
confidence: 99%